2022
DOI: 10.1002/bbb.2432
|View full text |Cite
|
Sign up to set email alerts
|

Biomass dry matter yield of willow and Miscanthus in low‐input cropping on heavy clay soils in Ukraine

Abstract: In Ukraine, 6.5 million hectares of agricultural land characterized by heavy clay soil could be available for sustainable bioenergy crop cultivation because they are considered marginal for food crop cultivation. This study investigated the biomass dry matter yield (DMY) of willow (Salix triandra L. and Salix viminalis L.) and Miscanthus (Miscanthus × giganteus Greef et Deuter) at two experimental sites with heavy clay in Ukraine. To promote plant rooting and adaptation in the first year of cultivation under l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…Plantation A covers 30 hectares, Plantation B covers 0.045 hectares, Plantation C covers 0.1 hectares, whilst Plantation D is 1 hectare. Earlier studies confirmed the good growth of M × g in the Czech Republic (Jeżowski et al 2017;Janota et al 2023), Croatia (Bilandžija et al 2021), and Ukraine (Prysiazhniuk et al 2022;Nedilska et al 2023). Plantations A and D were established on the agricultural land and plantations B and C were established at the slightly contaminated by TEs land (non-agricultural).…”
Section: Characteristics Of M × G Plantations (Location Average Tempe...mentioning
confidence: 67%
“…Plantation A covers 30 hectares, Plantation B covers 0.045 hectares, Plantation C covers 0.1 hectares, whilst Plantation D is 1 hectare. Earlier studies confirmed the good growth of M × g in the Czech Republic (Jeżowski et al 2017;Janota et al 2023), Croatia (Bilandžija et al 2021), and Ukraine (Prysiazhniuk et al 2022;Nedilska et al 2023). Plantations A and D were established on the agricultural land and plantations B and C were established at the slightly contaminated by TEs land (non-agricultural).…”
Section: Characteristics Of M × G Plantations (Location Average Tempe...mentioning
confidence: 67%